A conspectus of the flower fly genus Allograpta (Diptera: Syrphidae) with description of a new subgenus and species - Mengual, Ximo; Ruiz, Carlos; Rojo, Santos; Ståhls, Gunilla; Thompson, F. Christian (Zootaxa, 2009)
A new subgenus [Allograpta (Costarica Mengual & Thompson), type Allograpta zumbadoi Thompson], and one new species [Allograpta (Costarica) nishida Mengual & Thompson; type-locality: Costa Rica, type-depository: Instituto Nacional de Biodiversidad de Costa Rica] of flower flies (Diptera: Syrphidae) are described from the Neotropical biotic region. A checklist of the world species of Allograpta including synonyms is provided, and a key to and diagnoses of the subgenera are also supplied. The phylogenetic relationships among Allograpta species, representing all hitherto detected morphological diversity of the genus, and related genera were studied under parsimony based on morphological characters.